The Impact of Job Satisfaction and Job Characteristics on Turnover Intention in Palestine - Yaghi, Maysaa Saleh Mahmoud (2011)
The purpose of this research is to determine the relationship between employee job satisfaction, job characteristics and turnover intention. It also tries to identify which among the independent variables are the most important factors that explain turnover intention in one of the hotel organizations in Palestine. The research done by mean of survey, a questionnaire was distributed to 100 randomly selected respondents. The data was analyzed by using SPSS version 16. The findings of the study indicate that there is a significant negative relationship between the five dimensions of job satisfaction and turnover intention. Moreover, the findings from the correlation analysis revealed that a job characteristic is negatively and significantly correlated with turnover intention. It was found that job satisfaction is the most important relates to reduce employee turnover intention.